Development of FRACAS-CT module with FRAPCON4.0P01 for simulation of mechanical behaviors for accident-tolerant fuel cladding in a reactor. Issue 8 (3rd August 2019) - Kim, Dong-Hyun; Kim, Hyochan; Shin, Changhwan; Kim, Hak-Sung
ABSTRACT: In order to evaluate the mechanical behaviors of accident-tolerant fuel (ATF) cladding under reactor conditions, a new analytical module, termed FRACAS-CT, was developed. A mechanical model of FRACAS-CT was formulated based on thick-wall theory to consider the multi-layered structure of ATF cladding. Two statuses of a pellet-cladding gap, that is, open and closed, were described by several boundary conditions of pressures, inside radial displacements, and axial strains of the multi-layered ATF cladding. The FRACAS-CT model was verified by comparison with an equivalent finite element (FE) model and was implemented into FRAPCON4.0P1 with consideration of creep and stress relaxation behaviors of the multi-layered ATF cladding. After the implementation, code verification work was performed, and finally, mechanical behaviors and fuel performance of the multi-layered ATF cladding were calculated under normal operating conditions. As a result, the implemented FRACAS-CT can simulate the mechanical response and fuel performance of the multi-layered ATF cladding.